Indonesia’s Islamic Networks in Germany: The Nahdlatul Ulama in Campaigning Islam Nusantara and Enacting Religious Agency - Pribadi, Yanwar (Journal of Muslim minority affairs, 2022)
This article discusses Indonesia’s largest Muslim organization, the Nahdlatul Ulama (the NU), in campaigning Islam Nusantara, the NU’s version of moderate Islam, and enacting religious agency in Germany. The NU has expanded its networks by establishing special branches (PCI NU) across the globe. In Germany, the special branch was established in 2011. This paper specifically investigates organizational projects, religious practices of the NU people, and the campaign of moderate Indonesian Islam. My analysis of the results of ethnographic fieldwork consisting of in-depth interviews, casual chats, and hang-outs in the organization’s meetings and gatherings in Germany and Indonesia shows that PCI NU Germany is extending its transnational networks, claiming its religious agency, and strengthening its version of moderate Islam overseas in an effort to make its voices heard within Islamic communities and broader public in the host country and maintain socio-religious connections with the home country.